Kontekstualisasi Konsep Moderat dalam Al-Qur’an: Analisis QS. Al-Baqarah [2]:143 - Mustofa , Faiz Wildan (Sunan Kalijaga Islamic State University, 2022)
This study explores the issue of religious moderation in Indonesia, particularly within the context of QS. al-Baqarah [2]: 143, a verse frequently cited as foundational to the concept of moderation. Amidst the ongoing political climate, the issue of intolerance has become increasingly pertinent, exacerbated by the rise of social media and the influence of political buzzers who often distort information for specific agendas. The research aims to explore how the concept of religious moderation is interpreted by the community and how this interpretation is shaped from textual sources to everyday practices. Employing Hans-Georg Gadamer's hermeneutic method, the study analyzes the term “ummatan wasaṭan” in QS. al-Baqarah [2]: 143, with a focus on the socio-historical context of the text's revelation and its relevance to contemporary life. The findings reveal that the public's understanding of religious moderation is frequently misconstrued as either passive or inflexible, whereas it should be comprehended as embodying fairness and balance. Through descriptive-analytical text analysis, the study concludes that religious moderation, consistent with Gadamer's theory, involves an interplay between the horizon of the text and the horizon of the reader, facilitating a deeper and more contextually relevant understanding of the text in the present day.